Fonte tipográfica Clarim Fonética : um tipo de letra ao som da língua portuguesa - Reis, Jorge dos, 1971- (2017)
The typeface or typographic font Clarim Fonética is an alphabet that takes the phonetics of the vowels and consonants of the Portuguese language to reach its forms and so graphically shape them from the individual sound of each one. In this way the student can learn to read with an immediate visualization of the sound of each letter of the Portuguese — being the phoneme-grapheme connection absolutely direct and noticeable, without altering the traditional orthography